Political corruption and scandals in Japan - Carlson, Matthew (Cornell University press, 2018)
Understanding corruption in Japanese politics -- Scandals in early postwar Japan, 1948-1978 -- Scandals and reform, 1979-2001 -- Scandals and reform, 2002-2016 -- Bureaucratic corruption and political scandals -- Sex and campaign finance scandals -- Election law violations as political corruption